Estimation of a growth rate model for international business tourism - Carvalho, Pedro (2022)
The aim of this paper is to understand the factors influencing business tourism on a global scale, in order to assess the competence of the countries in this tourism segment and prescribe them guidelines for action. For the development of data analysis, a growth rate model was estimated and a sample of 136 countries for the years 2005 and 2009 was collected. Results reveal that, for the development of policies to stimulate the growth in the business tourism segment, countries should develop measures that encourage capital investment in tourism, leisure tourism and trade openness. Economic agents should also focus their investments in equipment that creates value throughout the tourism supply chain, in particular, in transport and equipment for entertainment and culture.